A Rare Presentation of Sarcomatoid Carcinoma of Duodenum: A Case Report - Jonathan Vincent Reyes MD; Tasur Seen MD; Bhanu Singh MD; Aaron Walfish MD (SAGE Publishing, 2022)
Sarcomatoid tumors are very rare biphasic tumors characterized by a mixture of malignant epithelial and mesenchymal cells that have been usually identified in the lungs with other documented cases in skin, bone, thyroid gland, salivary glands, breast, and genitourinary and gastrointestinal systems. They have an incidence estimated to be 0.5 to 0.8 per 100 000 per year. Three classic features include the presence of a genuine sarcomatous component, no transitional zone between carcinomatous and sarcomatous components, and immunohistochemistry of the sarcomatous component that is positive for mesenchymal markers and negative for epithelial markers. Sarcomatoid carcinoma of the gastrointestinal tract is rare but more commonly found within the stomach, gallbladder, and esophagus. Small bowel involvement is very rare.